Taiwanese Elementary Students’ Creativity, Creative Personality, and Learning Styles: An Exploratory Study (Alberta Journal of Educational Research, 2015)
In the field of education, creativity has been viewed as an important ability for children’s development. The recognition of different learning styles is also important for both teachers and learners. Although a handful of studies have examined the relationship between creativity and personality, or between creativity and cognitive style, few have assessed creativity, creative personality, and learning preferences simultaneously. Thus, the purpose of this study is to explore possible linkages between these three variables in Taiwanese children. More centrally, the research empirically probes into relating the personality and cognitive-style profiles of children, with creativity as a byproduct. The major finding of this research is that creative personality is positively related to creativity. Additionally, the results of multiple regression indicated that, among the variables studied, creative personality is the only valid variable for the prediction of creativity. Unexpectedly, none of the learning dimensions served as good predictors of creativity.Dans le domaine de l’éducation, on perçoit la créativité comme capacité importante au développement des enfants. Il est également important, tant pour les enseignants que les élèves, que l’on reconnaisse différents styles d’apprentissage. Si une poignée d’études se sont penchées sur le rapport entre la créativité et la personnalité, ou la créativité et le style cognitif, peu d’études ont porté à la fois sur la créativité, la personnalité créative et les préférences en apprentissage. L’objectif de cette étude est justement d’explorer les liens potentiels entre ces trois variables chez des enfants taiwanais. Plus précisément, cette recherche empirique met en lien la personnalité et le style cognitif des enfants avec la créativité comme sous-produit. Les conclusions indiquent qu’une personnalité créative est en corrélation positive avec la créativité. De plus, les résultats d’une analyse de régression multiple indiquent que parmi les variables étudiées, la personnalité créative est la seule avec un caractère prédicteur valide pour la créativité. Contrairement aux attentes, aucune dimension d’apprentissage n’a servi de bon prédicteur de créativité.